Perancangan Sistem Kontrol Kecerdasan Pada Segway Beroda Dua Berbasis Matlab/Simulink - Yuda Saputra, Dadang; Widhiada, I Wayan; Adi Atmika, I Ketut (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstractt Segway is a means of electric transportation that is flexible and easy to ride. The Segway is also a power-efficient vehicle so it can be an environmentally friendly alternative to short-distance transportation. In this research, the segway will only be balanced in a static state by using intelligent Fuzzy Logic Control which will balance when the segway is tilted at an angle and reads the tilt angle with a maximum angle of 15 ? forward and back. Segway uses the MPU6050 sensor based on the Arduino microcontroller with make control using MATLAB and simulink software. The sensor reads the change in angle so when the reading angle changes to a maximum angle of 15 the DC motor will move the other way around and Fuzzy Logic Control tries to balance it with a minimum response signal of maximum overshoot <5%, error signal <5% and settling time less than 5 seconds as standard robotics. Fuzzy logic control uses rules that have been made in such a way as to balance the segway. And obtained at a maximum slope of 15? maximum overshoot 3%, error percentage 4.7% and settling time 4 seconds then on a slope -15? maximum overshoot 26.6%, percentage error 2.8% and settling time 2 seconds. Keywords: Segway, Arduino, Balancing Robot, Fuzzy Logic, Matlab